Diseño de un plan de mejoramiento para equipos de trabajo en la compañía Carbonsteel Petroleum (2016)
The project presents the way how you should form effective teams, the importance of communication in every way to the team's effectiveness and compliance goals, the role of leadership, responsibility, commitment and trust as important aspects of this. Contemplate each of the aspects by which teams do not work, and this is where our research focuses within the company Carbon steel Petroleum , identifying those weaknesses and emphasizing the results obtained for the creation and implementation of a plan improvement within the company , making combat internal problems and meeting goals.